2007
DOI: 10.1007/s00425-007-0546-7
|View full text |Cite
|
Sign up to set email alerts
|

Spinach SoHXK1 is a mitochondria-associated hexokinase

Abstract: Hexokinase, a hexose-phosphorylating enzyme, has emerged as a central enzyme in sugar-sensing processes. A few HXK isozymes have been identified in various plant species. These isozymes have been classified into two major groups; plastidic (type A) isozymes located in the plastid stroma and those containing a membrane anchor domain (type B) located mainly adjacent to the mitochondria, but also found in the nucleus. Of all the hexokinases that have been characterized to date, the only exception to this rule is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 40 publications
(47 reference statements)
1
27
0
Order By: Relevance
“…However, gin2 plants remain small and dark green and show little cell expansion, supporting the role of HXK1 in promoting cell expansion and growth in roots, leaves and inflorescences under enhanced light conditions (Moore et al, 2003). In transgenic tomato plants, displaying higher sugar sensitivity than Arabidopsis plants, HXK1 overexpression inhibits growth and chlorophyll accumulation and promotes senescence (Dai et al, 1999;Granot, 2007). Thus, HXK1-mediated signaling can promote or repress growth, depending on the intrinsic glucose levels and glucose sensitivity of the plants.…”
Section: Hxk1 As a Glucose Sensormentioning
confidence: 87%
“…However, gin2 plants remain small and dark green and show little cell expansion, supporting the role of HXK1 in promoting cell expansion and growth in roots, leaves and inflorescences under enhanced light conditions (Moore et al, 2003). In transgenic tomato plants, displaying higher sugar sensitivity than Arabidopsis plants, HXK1 overexpression inhibits growth and chlorophyll accumulation and promotes senescence (Dai et al, 1999;Granot, 2007). Thus, HXK1-mediated signaling can promote or repress growth, depending on the intrinsic glucose levels and glucose sensitivity of the plants.…”
Section: Hxk1 As a Glucose Sensormentioning
confidence: 87%
“…It has been shown that in several mature and developing plant tissues, multiple HK isoforms are expressed with different kinetic properties and subcellular localizations. The HKs are found in cytosol, bound to the mitochondrial membrane, or in stroma of plastids in plant cells (Miernyk and Dennis, 1983;Galina et al, 1995;Damari-Weissler et al, 2007). Beyond its obvious role in glycolysis regulation, HK activity may also function as a sugar sensor, triggering a signal transduction pathway in plants (Rolland et al, 2006).…”
mentioning
confidence: 99%
“…These observations suggest a different type of association of mt-HK with plant mitochondria. The binding of mt-HK with mitochondria in many plants involves a common N-terminal hydrophobic membrane anchor domain of about 24 amino acids that is related to the membrane targeting, but the exact mechanism of association is unknown (Damari-Weissler et al, 2007).…”
mentioning
confidence: 99%
“…In spinach (Spinacia oleracea) leaves, SoHXK1 has been reported, based largely on subcellular fractionation studies, to be associated with the external plastid envelope (Wiese et al, 1999). However, a more recent study has shown that SoHXK1 has an N-terminal membrane anchor that is similar to known mitochondrialassociated HXKs and that the GFP fusion protein is expressed only in mitochondria (Damari-Weissler et al, 2007). Available evidence suggests that plastidlocalized HXKs might occur only in the stroma and possibly stromules , and might occur most abundantly in certain sink tissues (Giese et al, 2005).…”
mentioning
confidence: 99%
“…AtHXK1 has an N-terminal 24-amino acid peptide that is predicted to function as a targeting domain to mitochondria (Predotar; http://genoplante-info.infobiogen.fr/predotar; see also Olsson et al, 2003;Damari-Weissler et al, 2006). When expressed in tobacco (Nicotiana tabacum) protoplasts, AtHXK1-GFP expression was associated only with mitochondria (Damari-Weissler et al, 2007). On the other hand, based on a protoplast lysis protocol using Triton X-100, Yanasigawa et al (2003) reported that AtHXK1 occurs at least in part in the nucleus of isolated protoplasts.…”
mentioning
confidence: 99%